2020
DOI: 10.3390/nu12020310
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Serum Omega-3 and Omega-6 Polyunsaturated Fatty Acids: Exploratory Analysis of the Sex-Specific Effects and Dietary Modulation in Mediterranean Subjects with Metabolic Syndrome

Abstract: Many early studies presented beneficial effects of polyunsaturated fatty acids (PUFA) on cardiovascular risk factors and disease. However, results from recent meta-analyses indicate that this effect would be very low or nil. One of the factors that may contribute to the inconsistency of the results is that, in most studies, genetic factors have not been taken into consideration. It is known that fatty acid desaturase (FADS) gene cluster in chromosome 11 is a very important determinant of plasma PUFA, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 147 publications
(333 reference statements)
1
41
0
Order By: Relevance
“…LA and ALA are converted to longer chain PUFA by a consecutive series of reactions, including desaturation in the presence of Fads1 and Fads2 , and elongation and oxidation [ 16 ]. Maternal and fetal blood fatty acid compositions are substantially influenced by the Fads1 genotype in Japanese population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LA and ALA are converted to longer chain PUFA by a consecutive series of reactions, including desaturation in the presence of Fads1 and Fads2 , and elongation and oxidation [ 16 ]. Maternal and fetal blood fatty acid compositions are substantially influenced by the Fads1 genotype in Japanese population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developmental programming of disease is often sex-specific, and maternal nutrition is known to affect offspring in a sex-specific manner [ 15 ]. Recent research has also demonstrated that the FADS genes are regulated by sex [ 16 ]. This suggests that any changes in placental function associated with an elevated maternal LA diet may be sex-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate gene studies and genome-wide association studies (GWAS) both yield strong evidence that FADS and ELOVL genes are related to PUFA levels [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] and human disease phenotypes, e.g. cardiovascular disease (CVD) [ 91 , 92 ], major depressive disorder [ 93 , 94 ], metabolic syndrome [ 88 , 95 ], obesity [96] , atopic dermatitis [83] , aging [ 97 , 98 ], spinocerebellar ataxia 38 (SCA38) [99] . FADS genetic studies also showed population differences in the capacity to biosynthesize HUFA [ 95 , 100 ].…”
Section: Fads and Elovl Biochemical Functionsmentioning
confidence: 99%
“…In mammals, mammalian malic enzymes are divided into three isoforms according to their subcellular localization and cofactor specificity. Cytosolic NADP + -dependent ME (ME1) is involved in the generation of cytoplasmic NADPH for the biosynthesis of fatty acids and steroids in the liver and adipose tissues ( Frenkel, 1975 ; Coltell et al., 2020 ). Mitochondrial NADP + -dependent ME (ME3) is found in brain, heart, skeletal muscle, and adrenal tissues, which may associate with the cycling of NADPH into the mitochondria ( Frenkel, 1975 ).…”
Section: Introductionmentioning
confidence: 99%